Implementation of Consumer Personal Data Protection in Ecommerce from the Perspective of Law No. 27 of 2022 - Sidi Ahyar Wiraguna; Abdullah Sulaiman; Megawati Barthos (Journal of World Science, 2024)
This research aims to analyze the implementation of the Personal Data Protection Law (PDP Law) No. 27 of 2022 in the e-commerce sector in Indonesia, with a focus on consumer data protection. The method used is normative juridical, focusing on analyzing relevant documents and regulations to outline the legal framework and its application in e-commerce practices. Sources of legal materials include laws and regulations, academic literature, and interviews with legal experts and e-commerce practitioners. The results show that e-commerce companies have made significant adjustments to comply with the PDP Law, including improved privacy policies and investments in data security technologies. However, challenges to the full implementation of the PDP Law remain, particularly regarding consumers' and companies' awareness and understanding of the rights and obligations stipulated in the PDP Law. While there has been an increase in consumer trust in e-commerce platforms, increasing consumer awareness and active participation in the protection of their data still requires further efforts. The implication of this study is that the PDP Law No. 27 of 2022 has provided a stronger and more comprehensive legal framework for consumer data protection in Indonesia's e-commerce sector. However, to maximize the effectiveness of this law, a concerted effort is needed between regulators, the e-commerce industry, and the wider public to improve education and awareness of personal data protection, as well as ongoing adjustments to data management practices by e-commerce companies.